Footprints Revisited or "Life in the Changed Space that I don't Know": Elke Erb's Poetry Since 1989 - Barbara Mabee (Studies in 20th & 21st Century Literature, 1997)
After the fall of the Wall, the lyrical correspondence of the East German writer Elke Erb with the Austrian experimental writer Friederike Mayröcker proved to be of great significance for Erb's process of reexamining perspectives and constituting a new poetic self. In a close reading of Erb's post-Wende texts, the article discusses Erb's reshaping of her poetic craft against the backdrop of her life in the former GDR and literarty discourses in unified Germany. The analysis of representative poetry focuses on three areas of Erb's poetry collections after 1989: critical reflections on life in the former GDR through linguistically playful strategies; unanchored existence in spaces of language that signify a suspicious stance toward language and signification; intertextuality in the form of "text-echoes" with Friederike Mayröcker. This essay argues that Erb's intense reading of Mayröcker between 1991 and 1994 is a unique model of female reader response.
Keywords: fall of the Wall; 1989; lyrical correspondence; lyric; East German; East Geramny; Elke Erb; Austrian; writer; Friederike Mayröcker; reexamining perspectives; perspective; constituting a new poetic self; poetic self; poetry; post-Wende; GDR; life; DDR; unified Germany; Germany; reflections on life; former; strategies; space; language; signify; text-echoes; female reader response; female